Automatic application update with user customisation integration and collision detection for model driven applications - Davis, Jon; Chang, Elizabeth (IAENG, 2011)
Enterprise Information Systems (EIS) applications are complex and incur significant costs and effort during version upgrades, which are further exacerbated by any customizations. Our temporal meta-data framework for EIS applications avoids or minimizes these upgrade issues by standardizing all update procedures as an updated set or stream of individual meta-data changes. Each change is applied sequentially for all changes between the previous and current meta-data models. Meta-data changes include the core application functionality plus meta-data changes for any local or unique customizations. The automated update process removes the need from developers to produce version specific update programs, and simplifies the end user’s meta-data EIS application update processes. Collision detection with third party customizations, known as Variant Logic, can precisely identify any potential conflict in advance, avoiding or reducing compatibility rework effort for customizations.